The spirit of Zoroastrianism - Skjærvø, Prods O. (Sacred literature series., 2011)
Zoroastrianism is one of the world's oldest religions, though it is not among the best understood. Originating with Iranian tribes living in Central Asia in the second millennium BCE, Zoroastrianism was the official religion of the Iranian empires until Islam superseded it in the seventh century AD. Centered on the worship of Ahura Mazda, the All-knowing Ruler, Zoroastrianism follows the practices and rituals set out by the prophet Zarathustra, according to the Indigenous tradition. As one of the world's great religions, Zoroastrianism has a heritage rich in texts and cultic practices. The texts are often markedly difficult to translate, but in this volume, Prods Oktor Skjærvø, professor of ancient Iranian languages and culture at Harvard, provides modern and accurate translations of Zoroastrian texts that have been selected to provide an overview of Zoroastrian beliefs and practices. In a comprehensive introduction to these sacred texts, Skjærvø outlines the history and essence of Zoroastrianism and discusses the major themes of this the first fully representative selection of Zoroastrian texts to be made available in English for over a century.